Comparison of the effects of weekly and biweekly intravenous CERA administration on erythropoiesis: A randomized controlled trial. Issue 4 (22nd January 2021) - Kawai, Yuki; Toya, Yoshiyuki; Wakui, Hiromichi; Fujikawa, Tetsuya; Ueda, Eiko; Azushima, Kengo; Mitsuhashi, Hiroshi; Kawano, Tomoyuki; Kuji, Tadashi; Yamaguchi, Satoshi; Ohnishi, Toshimasa; Tamura, Kouichi
Abstract: Although continuous erythropoietin receptor activators (CERAs) are widely used erythropoiesis‐stimulating agents for correcting renal anemia in patients undergoing hemodialysis (HD), few reports have examined weekly CERA administration. In this randomized controlled trial, we compared the efficacy and changes in the parameters of iron metabolism and erythropoiesis between weekly and biweekly CERA administration. In total, 120 patients undergoing maintenance HD were randomized to the weekly or biweekly group. The primary end point was the total CERA dose needed to maintain the target hemoglobin (Hb) levels during a 12‐week evaluation period. There was no significant difference in the total dose between the weekly and biweekly groups (median 175.0 [interquartile range (IQR) 93.8–337.5] µg/12 weeks vs. 300.0 [IQR 125.0–375.0] µg/12 weeks, P = .18). The mean Hb levels during the evaluation period were 10.9 ± 0.8 g/dL in the weekly group and 10.7 ± 0.8 g/dL in the biweekly group ( P = .25). Weekly CERA administration was well tolerated. Weekly CERA administration similarly managed anemia as biweekly administration in patients undergoing HD. Abstract : Patients undergoing hemodialysis were randomized to once‐weekly or biweekly continuous erythropoietin receptor activator (CERA) treatment for 12 weeks. There were no differences in the total CERA dose to maintain hemoglobin levels between two groups.